ECOTHEOLOGICAL VALUES IN ENVIRONMENTAL JOURNALISM - Moebin, Amrullah Ali; Setyawan, Wahyu Eka; Natsir, Ahmad (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
This article aims to reveal the role of eco-theology in environmental journalism which has rarely been discussed by researchers. This article fills the void that is still not filled. Religion for journalists is appointed as a frame to make news raised in religious moral values. This leads to a question, what is the role of religion (eco-theology) in environmental journalism? After analyzing various objects in the form of books through literature study, this article concludes several things. Among them, has religion has laid down very deep principles of environmental ethics? however, in the reality of human life, especially in Indonesia, it is still so busy with studies of religious formalities. This has resulted in views on issues related to the environment that are less attractive to religious adherents. Second, the environmental ethical values contained in religion can be an inspiration in environmental coverage. This will, as expected by this research, make environmental journalists stand on eco-theological norms to be more pro-environmental conservation.